NEW NUMERICAL SIMULATION FOR THE FRACTAL-FRACTIONAL MODEL OF DEATHLY LASSA HEMORRHAGIC FEVER DISEASE IN PREGNANT WOMEN WITH OPTIMAL ANALYSIS - Chu, Yu-Ming; Rashid, Saima; Sultana, Sobia; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2023)
When it comes to human care service challenges, it is critical to understand the dynamic behavior of the associated contagious diseases because non-Markovian effects play a significant role in their spread. This investigation takes a look into an etiological model directly linked to the complexities of Lassa hemorrhagic fever disease in pregnant women in Africa. This is a bacteriostatic fever and an outbreak illness. The aforesaid ailment in expectant mothers has adverse implications that first popped up in Africa. The etiological model was constructed for the first time utilizing a recently designed fractal-fractional (FF) operator based on the power law, exponential decay, and Mittag-Leffler kernels with fractional order and fractal dimension. We construct three schemes of successive approximations based on FF operators using Lagrange polynomials, and the fundamental reproducing number is determined to be Script capital R0. The existence and uniqueness of the suggested model's mathematical technique are examined. The endemic and disease-free equilibria are also calculated. Eventually, simulated results of the framework are performed using the suggested numerical approach, and the outcomes in graphical representations quantify the effects of the projected and integrated characteristics and demonstrate that the ailment can be considerably governed or exterminated if the outbreak propagation rate is lessened and the rate of intervention is improved.
Keywords: Fractal-Fractional Caputo Derivative; Exponential Decay; Mittag-Leffler Function; Lassa Hemorrhagic Fever Disease; Lagrange Interpolation Polynomial